2017
DOI: 10.1016/j.bjm.2017.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity evaluation and comparison of methods of susceptibility for Klebsiella pneumoniae carbapenemase (KPC)-producing Enterobacter spp. isolates

Abstract: The production of KPC (Klebsiella pneumoniae carbapenemase) is the major mechanism of resistance to carbapenem agents in enterobacterias. In this context, forty KPC-producing Enterobacter spp. clinical isolates were studied. It was evaluated the activity of antimicrobial agents: polymyxin B, tigecycline, ertapenem, imipenem and meropenem, and was performed a comparison of the methodologies used to determine the susceptibility: broth microdilution, Etest® (bioMérieux), Vitek 2® automated system (bioMérieux) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 24 publications
3
12
1
1
Order By: Relevance
“…A study has reported that the sensitivity profile of microorganisms to antimicrobials can range from 0% to 4% when tested on Klebsiella pneumoniae (24) . Similar data were also found in the Serratia marcescens and Enterobacter cloacae species (25)(26) . It is important to emphasize the fact that the therapeutic limitation is a problem due to the rapid dissemination of resistance genes among the community, negatively impacting the outcome of hospitalized patients (24) .…”
Section: Discussionsupporting
confidence: 83%
“…A study has reported that the sensitivity profile of microorganisms to antimicrobials can range from 0% to 4% when tested on Klebsiella pneumoniae (24) . Similar data were also found in the Serratia marcescens and Enterobacter cloacae species (25)(26) . It is important to emphasize the fact that the therapeutic limitation is a problem due to the rapid dissemination of resistance genes among the community, negatively impacting the outcome of hospitalized patients (24) .…”
Section: Discussionsupporting
confidence: 83%
“…Determining resistance and susceptibility for imipenem-relebactam with disks and both strips for K. pneumoniae isolates was a challenge in some cases, because colonies grew within the zones of inhibition; the MIC was measured to the higher value or zone to the lower value. This has been described in other studies testing carbapenem resistance in K. pneumoniae carbapenemase (KPC)-producing Enterobacter isolates (21).…”
Section: Discussionsupporting
confidence: 54%
“…On par with the lower categorical agreement, the prevalence of mE's was higher than the other tests (11.7%). In contrast with some studies investigating different bacterial strains and antimicrobial agents (Biedenbach et al, 1993;Lehtopolku et al, 2012;Rechenchoski et al, 2017), the results of this study strengthen the validity of using the disk diffusion method for identifying resistance of APEC strains.…”
Section: Discussioncontrasting
confidence: 51%
“…Next to the paucity in gradient strip efficacy information, knowledge on the agreement between the other different AST methods is lacking for the specific APEC and ENRO combination. Most studies evaluating agreement between different AST methodologies have focused on human bacteria and fungi and antimicrobial agents frequently used in human medicine (Matar et al, 2003;Esteban et al, 2005;Rechenchoski et al, 2017).…”
Section: Introductionmentioning
confidence: 99%